Trace elements in the soils of the Tikves region - Boev, B. (Bulletin of the Geological Society of Greece, 2007)
The paper presents the results obtained during the investigations carried out for the availability of trace elements (Ni, Cd, Cr, Β) to the soils of the Tikves region. Examination by ICP-AES method were carried out on fifty samples taken in the vicinity of the villages of Begniste, Resava, Vozarci, Drenovo, Sirkovo, Manastirec, Sivec, Rosoman, Sopot, Vatasa, Kavadarci, the Beli Kamenja site as well as a number of samples collected between the places. The results obtained indicate high selenium quantities in the vicinity of Rosoman. Increased nickel concentrations, cadmium and boron along the Crna River course were also determined.